SISTEM INFORMASI KOPERASI SIMPAN PINJAM BERBASIS WEB (STUDI KASUS: KOPERASI ONIS MAJU BERSAMA) - Otomosi Gulo; Agung Wijoyo (CV. Multi Kreasi Media, 2024)
So far, the Onis Maju Bersama cooperative still uses a manual recording system with a book to process its data. The manual recording system will cause delays in managing the cooperative, and make it difficult for cooperative employees to track data deposits, data loans, and data payments on savings and loan transactions. The web-based savings and loan cooperative information system is a system that can assist cooperatives in managing data. This study discusses the design of a Web-Based Savings and Loans Cooperative Information System using the Rapid Application Development (RAD) system development method. The information system is made web-based with structured programming techniques, using the PHP programming language and MySQL database. The savings and loan cooperative information system was created to provide a system that can assist in recording member data, savings and loan transactions, and data officers more effectively using a computerized system The results of this study are information systems for data processing and data recording in the Onis Maju Bersama Cooperative, the documentation process is better, faster in managing data and minimizing data errors. With the hope that in the future this application can be developed so that there is a notification feature via the Whatsapp application to members when the installment payment due date is approaching.